Gertrudis Payás & Fabien Le Bonniec (eds): Intercultural Studies from Southern Chile. Theoretical and Empirical Approaches: Anmeldes af Torben Albertsen - Albertsen, Torben (Tidsskriftet Antropologi, 2021)
Gertrudis Payás & Fabien Le Bonniec (eds): Intercultural Studies from Southern Chile. Theoretical and Empirical Approaches. Anmeldes af Torben Albertsen